The Comparison of Kinship Terminology in the Yulin Dialect and in Cantonese - Hu, Wenmin (Lingua Posnaniensis, 2020)
The Yulin dialect is a sub-dialect of Cantonese, only used in Yuzhou and Fumian districts of the city of Yulin, located in the southeast of Guangxi Zhuang Autonomous Region, China. The kinship terms in Yue dialects include direct and indirect address terms, and usually are a combination of morphemes used to embody referential features (synthetic relation terms) and morphemes that distinguish the degree of kinship (ranking, collateral, spousal, generation and gender terms). This article offers a comparison, in terms of morphology, of kinship terms between the Yulin dialect and Cantonese. It is argued that the Yulin dialect and Cantonese have the same pattern of combining kinship terms, but approximately half of the compared kinship term logograms in the Yulin dialect are totally different from those in Cantonese as used in Canton, and the same terms are used in less than one-fourth of the cases.